Ontological models in OTSL - Anureev, I.S. (Інститут програмних систем НАН України, 2008)
OTSL is a language of description of ontological transition systems. Ontological transition systems are formalism for description of semantics of computer systems that combines transition systems with ontological models. In this paper, constructs of OTSL specifying the ontological models of ontological transition systems is presented. Formal semantics of these constructs is defined. OTSL – язык описания онтологических систем переходов. Онтологические системы переходов – формализм для описания семантики компьютерных систем, который комбинирует системы переходов с онтологическими моделями. В данной работе представлены конструкции OTSL, специфицирующие онтологические модели в онтологических системах переходов. Определена формальная семантика данных конструкций.